China After WTO : Shanghai Real Estate Development Trend - Yeming, Han (2005)
The study is about the real estate development trend of Shanghai. The development of the real estate of Shanghai is influenced by the total population, the investment of the real estate of Shanghai, the construction cost for each square meter and disposable income of Shanghai citizens.